DNA repair gene and MTHFR gene polymorphisms as prognostic markers in locally advanced adenocarcinoma of the esophagus or stomach treated with cisplatin and 5-fluorouracil-based neoadjuvant chemotherapy - Ott, Katja; Rachakonda, P. Sivaramakrishna; Panzram, Benjamin; Keller, Gisela; Lordick, Florian; Becker, Karen; Langer, Rupert; Büchler, Markus W.; Hemminki, Kari; Kumar, Rajiv (Annals of surgical oncology, 2011)
DNA repair plays an important role in chemoresistance to platinum-based therapy, and therefore polymorphisms in the genes may modulate therapeutic response. We assessed 12 polymorphisms in 7 DNA repair genes and 2 polymorphisms in the MTHFR gene for association with disease response and prognosis.